REMEDIES FOR BREACH OF CONTRACT BY THE SELLER UNDER THE CISG (American Journal of Interdisciplinary Research and Development, 2024)
The United Nations Convention on Contracts for the International Sale of Goods (CISG) provides a comprehensive framework for addressing breaches of contract in international sales. As one of the most significant treaties in international commercial law, the CISG aims to promote uniformity and predictability in cross-border transactions. This article examines the remedies available to buyers when sellers breach their contractual obligations under the CISG, drawing on relevant provisions, case law, and scholarly interpretations. The discussion includes the obligations of the seller, the differentiation between fundamental and non-fundamental breaches, and the range of remedies such as specific performance, avoidance of the contract, price reduction, and damages. Despite its comprehensive structure, the CISG faces challenges related to vagueness, interpretation issues, and the practical effectiveness of its remedies.